THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN OVERCOMING PESSIMISTIC ATTITUDES AND BUILDING STUDENT CONFIDENCE - Ali, Karimullah; Tamam, Badrut; Sutrisno, Sutrisno; Subairi, Subairi; Muhyatun, Muhyatun (Jurnal Konseling Pendidikan Islam, 2025)
The purpose of this research is to look at the efforts or strategies used by BK teachers at SMPN 1 Waru to help students reduce pessimistic attitudes and build their self-confidence in learning activities. This research was conducted using a qualitative approach, and descriptive qualitative methods. The data collection methods used are through interview techniques, observation, and documentation. Based on the data collection efforts carried out, it is known that the BK Teacher at SMPN 1 Waru Pamekasan uses a smooth approach when helping students develop their self-confidence in learning. Apart from that, BK teachers also use classical guidance services, individual counseling, and group counseling to help students reduce their pessimistic attitude toward learning.